Numerical investigation of combustion of biomass, methane, and gasoil fuels and emissions from a furnace chamber. (1st January 2016) - Shirneshan, Alireza; Jamalvand, Hossein
ABSTRACT: The aim of this study was to compare gaseous emissions from the combustion of conventional fuels (methane and gasoil) and biomass fuels (wood and peat) by the application of the CFD code FLUENT software in a furnace combustion chamber. According to the results, the combustion temperature obtained for conventional fuels was higher than it obtained for biomass fuels. Results also showed significantly lower emissions of CO2, NOx, and soot with the combustion of biomass compared to the methane and gasoil, but SO2 emissions from combustion of the conventional fuels were higher than that of biomass fuels. Also, results showed that the quantity of gaseous emissions is closely related to combustion temperature, molecular structure, and fuel characteristics.